Modern performing arts of Ukraine as lecture and practical lessons in the course with future teachers of musical art - Ihor Hevko; Olena Spolska; Xie Xiaonan; Wu Hongwei (Journal of Education, Health and Sport, 2022)
The purpose of the work is to highlight experimental methodical approaches to the representation of certain aspects of modern Ukrainian vocal art on the example of the organization of research, educational and performing activities of master's students of the Faculty of Arts of V. Hnatyuk TNPU.